2014
DOI: 10.1093/humrep/deu088
|View full text |Cite
|
Sign up to set email alerts
|

Major congenital anomalies in children born after frozen embryo transfer: a cohort study 1995-2006

Abstract: University Hospital of Oulu and Helsinki, Finland. THL covered the data linkages and the work of Annukka Ritvanen and Mika Gissler. There are no competing interests to be reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…For the birth defects, our study did not indicate a significant difference between births after FET and births after fresh ET. The results from most previous studies are similar to this result, except for one study that found a higher risk for birth defects among births by FET (Belva et al 2008;Davies et al 2012;Pinborg et al 2013;Pelkonen et al 2014). In general, our result indicated that FET is a safe, convenient, effective method to use during ART treatment.…”
Section: Discussionsupporting
confidence: 89%
“…For the birth defects, our study did not indicate a significant difference between births after FET and births after fresh ET. The results from most previous studies are similar to this result, except for one study that found a higher risk for birth defects among births by FET (Belva et al 2008;Davies et al 2012;Pinborg et al 2013;Pelkonen et al 2014). In general, our result indicated that FET is a safe, convenient, effective method to use during ART treatment.…”
Section: Discussionsupporting
confidence: 89%
“…They concluded that singleton pregnancies following frozen versus fresh transfers were associated with better perinatal outcomes (antepartum hemorrhage RR 0.67, 95 % CI 0.55-0.81; preterm birth RR 0.84, 95 % CI 0.78-0.90; small for gestational age RR 0.45, 95 % CI 0.30-0.66; low-birth weight RR 0.69, 95 % CI 0.62-0.76; and perinatal mortality RR 0.68, 95 % CI 0.48-0.96) [45]. When comparing the risk of major congenital anomalies, no difference between the techniques was shown [46]. On the other hand, there is a report of an increased risk of macrosomia in singletons born after FET comparing with fresh embryo transfer [47].…”
Section: Discussionmentioning
confidence: 96%
“…An increased risk of high birth weight and being large for gestational age (LGA, above 90th percentile) was reported as well [23][24][25][26][27][28][29]. A higher risk of congenital malformations for infants born after cryopreservation compared to fresh ET is also described [30,31]. When comparing children born after FET with natural conception, an increased risk for preterm birth, LBW, very LBW and need for caesarean sections was found [6].…”
Section: Introductionmentioning
confidence: 95%